Preconcentration strategies in the processing of nickel laterite ores Part 4: Preliminary dewatering studies. (August 2015) - Quast, Keith; Connor, Jason N.; Skinner, William; Robinson, David J.; Addai-Mensah, Jonas
Highlights: Laboratory dewatering conducted on nickel laterite slurries in saline solutions. Samples tested were <38 μm products from stirred milling or cyclone overflows. Commercial flocculants at least doubled the sediment solids density compared to feed. Comparative settling behaviour explained by zeta potential measurements. Abstract: The aim of this paper is to address primary dewatering of nickel (Ni) slurry streams resulting from any form of aqueous processing. The test work was conducted to investigate primary dewatering of screened products from either stirred milling or overflows from a hydrocyclone. Settling tests for the stirred mill products were conducted in 2 M NaCl to simulate expected process water quality where these laterite processes are located. Primary dewatering of 10 wt.% <38 μm stirred mill products can be successfully implemented for the three Ni laterite ores in 2 M NaCl solutions. Sediment solid contents of >20 wt.% have been achieved for all three ore types without raking. Sediment consolidation was significantly increased in further tests using low shear rate raking at 0.1 rpm. Zeta potentials were measured as a function of pH for all the fine laterite samples and compared to the characteristics for some of the major ore components. The more rapid settling behaviour observed for the goethitic laterite slurries was explained by little particle–particle repulsion due to the tests being conducted close to the isoelectric point. The zeta potentials measured at the pH values where the settling tests were conducted for laterites containing higher amounts of silica and silicates were much higher, requiring higher additions of flocculant and settling to lower sediment solids densities. The high salt content (2 M NaCl) is expected to screen electrostatic interactions between the particles and enhance settling behaviour.